Foreign direct investment: a strategic approach towards sustainable economic growth in Saudi Arabia - Haga Elimam; Halah Alattas (Cogent Economics & Finance)
Foreign direct investment (FDI) is pivotal in boosting export competitiveness in developing nations, making it a key driver of economic progress. This study investigates the influence of FDIs on fostering sustainable economic growth in Saudi Arabia from 1980–2022. The autoregressive distributed lag (ARDL) model investigates the long-run association between them. The findings of this research highlight FDI’s crucial role in Saudi Arabia’s economic strategy. It is observed that FDI contributes to sustainable economic growth as this research found a positive and significant impact of FDI on sustainable economic growth. Moreover, the Granger causality test also advocates the bi-directional flow of causality between FDI and sustainable economic growth. Overall, this research underscores the need for enhanced FDI inflows and the careful management of investments to prevent economic distortions. This study recommends accelerating economic reforms, improving the investment climate, and updating legislation to align with evolving local and global economic conditions, providing a roadmap for sustaining economic growth through strategic FDI.